Teaching weak learners to solve non-routine mathematics problems. - Wan Bakar, Wan Norliza (Journal of Islamic, Social, Economics and Development, 2026)
Weak learners often struggle with non-routine mathematics problems because due to limited conceptual understanding, poor visualization skills and a reliance on rote procedures. Such challenges hinder their ability to develop problem solving strategies, which are essential for higher order thinking. This paper explores effective teaching approaches designed to support weak learners in engaging with non-routine problems. Using Polya’s problem solving frame work, combined with scaffolding,visualization techniques and metacognitive strategies ,the study highlights how teachers can guide students to better understand problem structures, devise strategies, and reflect on their solutions. Future research can be done to further implement this technique for helping weak students to be a better problem solver that will benefit the nations to become highly efficient person in their field of work.